The current state of the art in research on predictive maintenance in smart grid distribution network: Faults types, causes, and prediction methodsa systematic review - Mahmoud M.A.; Md Nasir N.R.; Gurunathan M.; Raj P.; Mostafa S.A. (MDPI AG, 2023)
Artificial intelligence; Electric power transmission networks; Fault detection; Internet of things; Predictive maintenance; Effective transmission; Exponential growth; Internet of Things (IOT); Prediction methods; Renewable energies; Smart grid systems; State of the art; Systematic Review; Smart power grids